'Ba Ba Black Sheep' (second verse) - Lynda; Awre, Gabrielle (The University of Hull, 2017)
This was an extra verse of Ba Ba Black sheep that Lynda sang to me and then a short conversation about the words e.g., the word 'frock'. Lynda sang this to her grandchildren who thought she'd got it wrong! Lynda had known this verse for most of her life and didn't know where it came from.